Dual conception of risk in the Iowa Gambling Task: effects of sleep deprivation and test-retest gap - Singh, Varsha (Frontiers in Psychology, 2013)
Risk in the Iowa Gambling Task (IGT) is often understood in terms of intertemporal choices, i.e., preference for immediate outcomes in favor of delayed outcomes is considered risky. According to behavioral economics, decision makers refrain from choosing the short-sighted immediate gain because, over time (10 trials), the immediate gains result in a net loss. Instead decision makers are expected to maximize their gains by choosing options that, over time (10 trials), result in net gain. However, task choices are sometimes made on the basis of the frequency of reward and punishment such that infrequent punishments are favored over frequent punishments. The presence of these two attributes (intertemporality and frequency) may correspond to the emotion-cognition dichotomy and reflect a dual conception of risk. Decision making on the basis of the two attributes was tested under two conditions: test-retest gap and sleep deprivation. An interaction between these two was expected to attenuate the difference between the two attributes (n=40 male). Analysis of the effects of IGT attribute type (intertemporal vs. frequency), sleep deprivation (sleep deprivation vs. no sleep deprivation), and test-retest gap (short vs. long) showed a significant effect of IGT attribute type thus confirming the difference between the two attributes. Sleep deprivation had no effect on the attributes, but test-retest gap and the three-way interaction between attribute type, test-retest gap, and sleep deprivation were significant. Post-hoc tests showed sleep deprivation and short test-retest gap to attenuate the difference between the two attributes. As expected intertemporal decision making benefited from repeated task exposure. The findings add to understanding of the emotion-cognition dichotomy and show a time-dependent effect of a universally experienced constraint (sleep deprivation).